2017
DOI: 10.1080/00918369.2017.1374066
|View full text |Cite
|
Sign up to set email alerts
|

Adding Insult to Injury: Sex, Sexual Orientation, and Juror Decision-Making in a Case of Intimate Partner Violence

Abstract: Societal definitions of intimate partner violence (IPV) are highly gendered and heteronormative, resulting in dissonance regarding cases of same-sex IPV. This study explored perceptions of IPV when the context of the case is inconsistent with societal norms regarding sex and sexuality. Mock jurors read a vignette describing a case of alleged IPV in which the sex and sexual orientation of the defendant were manipulated. Participants (N = 415) rendered a verdict and provided ratings of the defendant, victim, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 53 publications
4
21
0
Order By: Relevance
“…Future studies should also examine the impact of the victim's gender, a variable not explored within this study. There is a growing body of research suggesting that the defendant's, victim's, and juror's genders do not influence sentencing effects in isolation, but rather it is their interaction that elicits gendered-sentencing-leniency effects (Stanziani et al, 2018). In conjunction with this defendant-victim-juror gender interaction, researchers should seek to understand the role the defendant's and/or victim's sexual orientation plays in influencing trial outcomes, particularly in cases of IPV and IPH.…”
Section: Implications Limitations and Future Directionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Future studies should also examine the impact of the victim's gender, a variable not explored within this study. There is a growing body of research suggesting that the defendant's, victim's, and juror's genders do not influence sentencing effects in isolation, but rather it is their interaction that elicits gendered-sentencing-leniency effects (Stanziani et al, 2018). In conjunction with this defendant-victim-juror gender interaction, researchers should seek to understand the role the defendant's and/or victim's sexual orientation plays in influencing trial outcomes, particularly in cases of IPV and IPH.…”
Section: Implications Limitations and Future Directionsmentioning
confidence: 99%
“…In conjunction with this defendant-victim-juror gender interaction, researchers should seek to understand the role the defendant's and/or victim's sexual orientation plays in influencing trial outcomes, particularly in cases of IPV and IPH. A number of studies have found evidence to suggest that heterosexual female defendants and victims receive more favorable outcomes than legal actors of any other sexual orientation and gender combination (Russell, 2018;Stanziani et al, 2018); additional research would contribute to a more nuanced understanding of gender bias within the courtroom.…”
Section: Implications Limitations and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although evidence suggests that victim and perpetrator gender impact legal-decision making in other types of crime (Mazzella & Feingold, 1994;, to date, research on the impact of gender and sexual orientation-related stereotypes on judgements about same-sex IPV is limited, and what has been conducted has produced mixed results (Harris & Cook, 1994;Seelau, Seelau & Poorman, 2003;Seelau & Seelau, 2005;Stanziani, Cox, & Coffey, 2018, Stanziani, Newman, Cox, & Coffey, 2019Little & Terrance, 2010;Wasarhaley, et al, 2015). As such, this thesis draws on explanatory frameworks that have been developed in the allied literatures of sexual assault (McKimmie, et al, 2014) sexual harassment (Wayne, Riordin, & Thomas, 2001) and sexism more broadly (Biernat & Manis, 1994;Eagly & Diekman, 2005;Moss-Racusin, Phelan, & Rudman, 2010), in order to provide insight into how people make legally relevant decisions and judgements about IPV in same-sex relationships between men, and between women.…”
Section: The Role Of Stereotypes In Legal Decision-makingmentioning
confidence: 99%
“…In addition, victims of female perpetrated violence are held more responsible for the violence compared to when the perpetrator is male (Seelau et al 2003). While violence with a male perpetrator and female victim is evaluated as more serious (Taylor & Sorenson, 2005), and the perpetrator judged as more morally responsible (Stanziani, et al, 2018) than any other victim and perpetrator combination, it has also been found that when the victim is a gay man or a lesbian woman, the odds of being assigned equal fault for the assault are highest (Taylor & Sorenson, 2005). In accounting for this, Taylor and Sorenson (2005) suggest that this occurs because people apply gender stereotypes to same-sex partners, and as a consequence, perceived them to be more equal than different-sex partners in terms of physical strength and potential to cause injury.…”
Section: Perceptions Of Same-sex Intimate Partner Violencementioning
confidence: 99%